Estudo do potencial de utilização da biomassa de Luffa cylindrica na descontaminação de efluentes contendo íons metálicos e corantes têxteis - Oliveira, Elisangela Antonieta de (2007)
The study to evaluate the capacity of removal of the dyes Red Procion H-E7B and Yellow Procion H-E4R in aqueous solution by the dried fruit of Luffa cylindrical (a quite common tropical plant in Brazil) in natura was carried out in batch system and also in columns of fixed bed. In pH 2.5 occurs the largest removal of the dyes, being necessary 60 minutes to reach the sorption equilibrium, and obeying a pseudo-second order kinetics. For the dye sorption, the surface of the raw biomass is constituted mainly by homogeneous zones, as the experimental data are better fitting to the Langmuir isotherm model. The use of a solution of NaOH 0.001 mol L-1 resulted in the desorption of 77% and 86% for the red and yellow dyes, respectively. These studies showed, also, to be possible the reutilization of the column containing the biomass without loss in the efficiency of the sorption, at least for three times. The removal of the ions Pb(II), Cd(II), Cu(II) and Zn(II) of aqueous solutions using the biomass of Luffa c., raw and modified with NaOH, was also evaluated in batch systems. The greatest removal of the ions was found at pH 5, and the sorption equilibrium was reached within 30 minutes. The modified biomass had sorption capacities for the metal ions higher than unmodified Luffa c.. The experimental data indicated that the sorption process of the metallic ions can be better described according to the Freundlich isotherm model, suggesting a heterogeneous surface. The kinetic study implied that the sorption of the metal ions into Luffa c. follows the kinetic model of pseudo-second order, and also the presence of more than a sorção mechanism. HCl showed the largest efficiency, although without a total recovery of the metal ions. Once defined the sorption conditions, the potential of Luff c. for the removal of metal ions from effluents of galvanoplasty and batteries industries (modified biomass) and, also, for the removal of the Yellow Procion H-4R and Red Procion H-E7B dyes from synthetic and real textile effluents (raw biomass) was investigated in batch and fixed bed column systems. The biomass of Luffa c. showed a quite high efficiency in the batch system - 56% without pH adjustment and 84% with previous pH adjustment for the synthetic effluent of Red Procion H-E7B, and 36 and 85%, without and with pH adjustment, respectively, for the effluent containing Amarelo Procion H-E4R. In the experiments with the effluent of a local textile industry, containing the Red Procion H-E7B, a great efficiency was observed in the dye sorption - 75 and 88% with and without pH adjustment, respectively, in batch system, and 94% in the system of fixed bed columns. These data indicate that the biomass of Luffa c. is able to significantly reduce the dye amount in the effluent. However, due to the quite high dye concentration in the dying effluent, the sorption process was not able to reach the limits imposed by the Brazilian legislation; therefore, the use of combined treatments is suggested. In system of fixed bed column, using the biomass modified with NaOH, the efficiency of the removal of Cd(II), Cu(II), Pb(II) and Zn(II) from galvanoplasty and battery effluents was greater for Pb(II) - 61% and 44%, respectively. The removal of Cu(II) and Zn(II) was greater in the experiments with the effluent of the galvanoplasty, but the efficiecy was less than 50%.